2012
DOI: 10.4236/epe.2012.43023
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Diesel Grade Fuel Transformed from Polypropylene (PP) Municipal Waste Plastic Using Thermal Cracking with Fractional Column Distillation

Abstract: Day by day worldwide use of plastics is increasing because of their light weight and durable characteristics. Waste plastics are major environmental problems all over the world. Waste plastics are not biodegradable , it remains in the landfill for a long period of time causing vegetation and aquatic ecosystem dilemmas. Abandoned waste plastic thrown into the ocean causes friction of ocean waves and then broken down by sunlight into small pieces and takes the shape of plastic like soup. Aquatic organism mistake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
(6 reference statements)
1
10
0
Order By: Relevance
“…Sweet oil is more preferable than the sour due to its applicability to produce most of the refined products [18,27]. Another Waste mixed plastic [12] Waste HDPE [27] Gulf fuel oil [28] 1 D e n s i t y @ 50 0 30 40 50 60 70 80 90 100 110 120 130 140 150 160 170 180 190 200 210 220 100 50 0 30 40 50 60 70 80 90 100 110 120 130 140 150 160 170 180 190 200 210 220 100 50 0 30 40 50 60 70 80 90 100 110 120 130 140 150 160 170 180 190 200 210 important attribute was found to be kinematic viscosity of liquefied hydrocarbon synthesized from waste plastic that was estimated to be 2.149 mm 2 /s at 40 ∘ C. As per the standard kinematic viscosities of fuel oil (3.5-9.7 mm 2 /s), oil formed by our method was found to be less viscous [20,30,31]. Calorific value of oil synthesized from pyrolysis of waste plastic was recorded to be 10,000 cal/g (41.86 MJ/kg), whereas Calorific values of various fuel oils, for example, diesel, gasoline, petrol and petroleum fuel are 44.8, 47.3, 48 and 43 MJ/Kg respectively [20,30,31].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Sweet oil is more preferable than the sour due to its applicability to produce most of the refined products [18,27]. Another Waste mixed plastic [12] Waste HDPE [27] Gulf fuel oil [28] 1 D e n s i t y @ 50 0 30 40 50 60 70 80 90 100 110 120 130 140 150 160 170 180 190 200 210 220 100 50 0 30 40 50 60 70 80 90 100 110 120 130 140 150 160 170 180 190 200 210 220 100 50 0 30 40 50 60 70 80 90 100 110 120 130 140 150 160 170 180 190 200 210 important attribute was found to be kinematic viscosity of liquefied hydrocarbon synthesized from waste plastic that was estimated to be 2.149 mm 2 /s at 40 ∘ C. As per the standard kinematic viscosities of fuel oil (3.5-9.7 mm 2 /s), oil formed by our method was found to be less viscous [20,30,31]. Calorific value of oil synthesized from pyrolysis of waste plastic was recorded to be 10,000 cal/g (41.86 MJ/kg), whereas Calorific values of various fuel oils, for example, diesel, gasoline, petrol and petroleum fuel are 44.8, 47.3, 48 and 43 MJ/Kg respectively [20,30,31].…”
Section: Resultsmentioning
confidence: 93%
“…From the distillation report of the liquefied hydrocarbon, it was found that boiling range of the oil is 71-390 ∘ C, which suggests the presence of a mixture of different fractions such as gasoline, kerosene, and diesel [17,20,[30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous authors have investigated the possible application of plastic waste pyrolysis oils as diesel fuel [202][203][204][205][206]. The research often involves fractionation since physical parameters such as boiling points, viscosities and densities are crucial for fuel applications.…”
Section: Fractionation Via Distillationmentioning
confidence: 99%
“…15), red mud, 16 Fe 2 O 3 (ref. 17) and activated carbons are crucial catalysts that have undergone testing in catalytic pyrolysis processes involving coal or waste plastic. 18 Nevertheless, the rapid deactivation and the expensive nature of commercial catalysts make the catalytic pyrolysis of waste plastic nancially unviable on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…Specically, Fe 2 O 3 has the ability to break down large hydrocarbon chains into smaller ones. 17 Additionally, the presence of unburned carbon in y ash can also serve as a catalyst, facilitating the conversion of heavy hydrocarbons into alkanes 18 Moreover, y ash contains activated carbon, a porous form of carbon treated with oxygen to enhance its pore structure and surface area, which can also function as a favorable catalyst to attain the desired hydrocarbon range for kerosene fuel. It has been projected that global ash production will reach approximately 430 million tons in the early 21st century, posing potential environmental challenges in its management.…”
Section: Introductionmentioning
confidence: 99%